PENGEMBANGAN BAHAN AJAR DRAMA BERBANTUAN MEDIA BOOK CREATOR PADA SISWA KELAS XI - Siti Hadijah; Fitriani Lubis; Frinawaty Lestarina Barus (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Teaching materials are learning resources used during learning, making it easier to convey lesson material information. Teaching materials are not only limited to printed books, but some are electronic based. One of the electronic-based teaching materials that can be used is electronic books. Electronic books are teaching materials that can meet students' needs for drama material. So it is necessary to develop electronic books on drama material using book creators in class XI high school. This research aims to (1) The process of developing drama teaching materials with the help of book creators, (2) The form of drama teaching materials with the help of book creator media. The development model used is the ADDIE model. With techniques and data collection from interviews with teachers in the field of study, observation, documentation and questionnaires. Results of questionnaire data from media experts and material experts. Development in this research uses the ADDIE model which has three stages, namely analysis, design, development. The results of this research show that in the media expert assessment, they received a percentage score of 96.42% in the